Pelatihan Manajemen Event sebagai Upaya Peningkatan Kompetensi Mahasiswa Olahraga dalam Pengelolaan Event (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
Event management is one of the competencies that sports students need to have to support their readiness to enter the workforce in the sports industry. However, students' practical experience in managing events is still limited, so a training program that can integrate conceptual learning with practical experience is needed. This community service activity aims to improve sports students' knowledge of event management through experiential learning-based training. The program was implemented using a participatory approach with a one-group pretest–posttest design involving 30 students from the Faculty of Sport and Health Sciences, Surabaya State University. The training consisted of lectures, discussions, case studies, workshops, and simulations of organizing sports events. Evaluation was carried out using a knowledge test and a participant satisfaction questionnaire. Data were analyzed descriptively, using the Shapiro–Wilk normality test, paired sample t-test, effect size (Cohen's d), and Normalized Gain (N-Gain). The results showed that the post-test score increased significantly compared to the pre-test (p < 0.001) with a Cohen's d value of 2.84 indicating a very large effect and an N-Gain value of 0.62 in the moderate category. Furthermore, participant satisfaction reached 90.45%, categorized as very good, particularly in terms of resource person competency and learning methods. These findings demonstrate that experiential learning-based training effectively enhances student knowledge while providing a positive learning experience relevant to the needs of organizing sporting events. This program has the potential to become a model for developing event management competencies that can be replicated in universities and sporting organizations.